2004
DOI: 10.1046/j.1540-8167.2004.03423.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomic Study on Atrial Fibrillation Using cDNA Microarray and Two‐Dimensional Protein Electrophoresis Techniques and Identification of the Myosin Regulatory Light Chain Isoform Reprogramming in Atrial Fibrillation

Abstract: Both cDNA microarray and two-dimensional polyacrylamide protein electrophoresis studies revealed characteristic changes in AF tissue. We demonstrated the reprogramming of myosin regulatory light chain isoform composition, with a significant increase of its ventricular isoform (MLC-2V).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 23 publications
2
35
1
2
Order By: Relevance
“…Even though steroid eluding pacing catheters were used, the pig model demonstrated the problematic tendency to encapsulate the electrodes, leading to the inability to pace the atria and to induce sustained AF. While several studies (6,(17)(18)(19) of RAP-induced AF in pigs have been published, none of these reports have models of AF in pigs of Ͼ6 wk in duration. There is inconsistency concerning the effect of AF on LV EF and atrial fibrosis in these published studies (see Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Even though steroid eluding pacing catheters were used, the pig model demonstrated the problematic tendency to encapsulate the electrodes, leading to the inability to pace the atria and to induce sustained AF. While several studies (6,(17)(18)(19) of RAP-induced AF in pigs have been published, none of these reports have models of AF in pigs of Ͼ6 wk in duration. There is inconsistency concerning the effect of AF on LV EF and atrial fibrosis in these published studies (see Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…18, 19 Moreover, a recent microarray study using a pig model of AF showed that the gene changes are more pronounced in the LA than the RA, with considerable overlap in the gene response. 20 Another previous study compared differences in 517 proteins that were expressed differently in the LAA between the SR and AF patients were associated with high-level functions and utilities of the biological system were identified. Metabolism-and cardiovascular disease-related proteins play an important role in the LAA tissue of AF patients.…”
Section: Main Findingmentioning
confidence: 99%
“…5 To explore the hypothesis that pmAF leads to upregulation of ventricular transcripts other than those encoding for contractile proteins, we used a genome-wide approach to compare atrial mRNA expression of patients with pmAF to atrial mRNA expression of patients with sinus rhythm (SR) as well as to ventricular (LV) gene expression. Our findings indicate that pmAF leads to repression of atrial transcriptional activity and induces a ventricular-like genomic signature in atrial myocardium.…”
mentioning
confidence: 99%